2023
DOI: 10.3390/foods12030503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Shogaol on Glucose Uptake and Intestinal Barrier Integrity in Caco-2 Cells

Abstract: As the main bioactive component in dried ginger, 6-shogaol has potential hypoglycemic activity, but its mechanism is still unclear. The process of carbohydrate digestion and glucose absorption is closely related to the enzymatic activity of epithelial brush cells, expression of glucose transporters, and permeability of intestinal epithelial cells. Therefore, this study explored the hypoglycemic mechanism of 6-shogaol from the perspective of glucose uptake, absorption transport, and protection of intestinal bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Given that in vivo experiments are difficult to represent the process, therefore we validated it by establishing an in vitro model. Relevant studies have shown that the intestinal epithelial cell monolayer model established by Caco-2 cells has been widely used for drug uptake transporter studies [ 36 , 37 ]. Therefore, we inoculated Caco-2 cells in the upper chamber of Transwell plates and cultured them for 21 d to construct the intestinal epithelial monolayer cell model, and when the resistance was > 500 Ω/cm 2 , we inoculated RWPE-1 cells in the lower chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Given that in vivo experiments are difficult to represent the process, therefore we validated it by establishing an in vitro model. Relevant studies have shown that the intestinal epithelial cell monolayer model established by Caco-2 cells has been widely used for drug uptake transporter studies [ 36 , 37 ]. Therefore, we inoculated Caco-2 cells in the upper chamber of Transwell plates and cultured them for 21 d to construct the intestinal epithelial monolayer cell model, and when the resistance was > 500 Ω/cm 2 , we inoculated RWPE-1 cells in the lower chamber.…”
Section: Methodsmentioning
confidence: 99%
“…31 To further verify our speculations, we analyzed the 16 S rDNA data. PICRUSt analysis has shown that some pathways contribute to the process of apoptosis (pertussis, 32 Type II diabetes mellitus, 33 pathogenic Escherichia coli infection, 34 and the RIG-I-like receptor signaling pathway 35 ) and intestinal tight junction (carbohydrate digestion and absorption 36 and pathogenic Escherichia coli infection 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In GM, the typical trend of hydroxytyrosol and tyrosol was not observed and there was an exponential increment of 6-gingerol during the 12 months of storage. For 6-shogaol, different studies have confirmed the in vivo and in vitro activity against lipid absorption [44]. However, for GI, the content of phenols from ginger remained constant throughout storage.…”
Section: Tpc α-Tocopherol Content and Individual Phenols By Uhplcmentioning
confidence: 97%